Growth Rate from Birth to Three Months of Breastfed and Non-Breastfed Infants Delivered in Hospitals at Owo Metropolis - Mustapha, R.A.; Oladapo, A.A.; Akinola, T.M.; Akinlotan, J.V.; Oluwagunwa, A.P. (International Journal of Child Health and Nutrition, 2017)
The growth rate from birth to three months of some breastfed and non-breastfed infants age 0 – 12 weeks delivered in hospitals at Owo metropolis was evaluated with a view to know the effect of breastfeeding on growth rate. A total of one hundred (100) breastfed and non-breastfed neonates were purposely selected in the neonatal sections of three hospitals in Owo, March 2012. Anthropometry measurement was used to assess growth rate for length, weight, head and mid upper arm circumference of the infants on weekly basis using standard length board, digital weighing scale and shakir tape for twelve weeks. Epi-info 2008 nutritional software was used to determine length for – age z-score, weight for – age z-score, Head and mid-upper arm for age z – scores. Data were analyzed using SPSS soft ware (version 17.0). Results show that the rate of growth in length per week ranged between 0.5 – 1.0cm within 4th to 12th weeks of growth while an average rate of growth in weight of 100 – 400g was discovered between 2nd to 6th weeks of growth among both breastfed and non-breastfed infants. Observation shows that between birth to 4th week formula fed babies tend to be leaner in weight compared to their breastfed counterpart which maintained stable weight within this period. The study shows that breastfeeding significantly (P> 0.05) affect rate of growth among the breastfed infants. Growth pattern of infant skewed toward – 2 and 0 when compared with the NCHS/CDC reference population growth curve. In all, 2% of the breastfed and 8% of non-breastfed were severely underweight. There is no alternative to breastfeeding at this critical stage of life for optimum growth of infants. Therefore, mothers should be encouraged to breastfeed exclusively for 6th months in order to achieve optimum growth and development.